2008
DOI: 10.1194/jlr.m800105-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid (CB2) receptor deficiency reduces the susceptibility of macrophages to oxidized LDL/oxysterol-induced apoptosis

Abstract: Macrophage apoptosis is an important process in the pathophysiology of atherosclerosis. Oxidized lowdensity lipoproteins (OxLDL) are a major component of lesions and potently induce macrophage apoptosis. Cannabinoid receptor 2 (CB2), the predominant macrophage cannabinoid receptor, modulates several macrophage processes associated with ongoing atherosclerosis; however, the role of CB2 in macrophage apoptosis is unknown. To determine if CB2 influences a macrophage apoptotic pathway relevant to atherosclerosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
2
23
0
2
Order By: Relevance
“…CB2R activation by THC inhibits atherosclerotic plaque progression in mice by inhibiting macrophage recruitment and anandamide inhibits inflammatory gene expression in endothelial cells, and consequently monocyte adhesion (Mach and Steffens, 2008). CB2 may influence atherosclerosis by modulating lesional macrophage apoptosis (Freeman-Anderson et al, 2008). Endocannabinoids might also mediate pro-atherosclerotic effects by inducing platelet activation (Mach and Steffens, 2008).…”
Section: Therapeutic Implicationsmentioning
confidence: 98%
“…CB2R activation by THC inhibits atherosclerotic plaque progression in mice by inhibiting macrophage recruitment and anandamide inhibits inflammatory gene expression in endothelial cells, and consequently monocyte adhesion (Mach and Steffens, 2008). CB2 may influence atherosclerosis by modulating lesional macrophage apoptosis (Freeman-Anderson et al, 2008). Endocannabinoids might also mediate pro-atherosclerotic effects by inducing platelet activation (Mach and Steffens, 2008).…”
Section: Therapeutic Implicationsmentioning
confidence: 98%
“…As described above, smooth muscle cells are crucially involved in the pathogenesis of atherosclerosis and restenosis. Moreover, there is evidence for a role of CB 2 receptors in macrophage apoptosis induced by oxidized LDL [147]. Oxidized LDL is a well-known trigger for atherosclerosis, which accumulates in macrophages within atherosclerotic lesions, resulting in foam cell formation [143].…”
Section: The Endocannabinoid System In Atherosclerosismentioning
confidence: 99%
“…Thus, macrophage apoptosis, at least in advanced lesions, could be considered as a proatherogenic factor triggering plaque instability and rupture [150]. Freeman-Anderson and colleagues investigated the effect of genetic CB 2 deficiency on oxidized LDL-induced apoptosis [147]. They found that the apoptosis rate was significantly reduced in peritoneal macrophages from CB 2 knockout mice as compared to wild-type animals.…”
Section: The Endocannabinoid System In Atherosclerosismentioning
confidence: 99%
“…As reviewed recently by Buckley [67], several studies have shown that certain macrophage processes associated with the development and progression of atherosclerosis are modulated by CB 2 receptors [196,201,202]. In a more recent study Freeman-Anderson et al [203] detected fewer apoptopic resident peritoneal macrophages in CB 2 gene-deficient mice than in wildtype mice after incubation with oxidized LDL (OxLDL) and 7-ketocholesterol (7-KC) a component of OxLDL. Caspase-3 and cleavage of its substrate PARP, as well as deactivation of the prosurvival kinase, Akt in response to 7-KC, were all attenuated in CB 2 gene-deficient mouse macrophages.…”
Section: Atherosclerosis and Restenosismentioning
confidence: 97%